The nexus between water, exergy, and economics in an optimal integrated desalination system with two configurations and four operation modes - Tayerani Charmchi, Amir Saman; Ifaei, Pouya; Yoo, ChangKyoo (Energy conversion and management, 2022)
[Display omitted] •A novel integrated system was proposed in 2 configurations and 4 operating modes.•Four new water-exergy nexus-based evaluation criteria were employed.•Some performance criteria improved by 3.7 times after many-objective optimization.•The robust double-compressor configuration is recommended for hot and dry regions.•The single-compressor configuration is more adaptable to environmental fluctuations. Numerous integrated desalination systems have been proposed to satisfy the growing global demand for freshwater. However, the responses of various optimal configurations have rarely been subject to advanced combined analyses. Here, a parallel-feed multi-effect evaporative desalination unit is integrated with a series double-effect water-lithium bromide absorption heat pump using thermo-mechanical components to propose a novel flexible system. The proposed hybrid multi-modal cooling-heating-desalination system can be configured as a single compressor or a double-compressor. Both configurations can operate in four modes, producing chilled and tap water (mode I); hot and tap water (mode II); tap water (mode III); or chilled, hot, and tap water (mode IV). The energy, exergy, and economics of the proposed system are modeled in an iterative nonlinear thermo-mathematical program. The base models are compared using exergoeconomic and novel water-exergy nexus-based evaluation criteria, their sensitivity is examined under each operation mode, and the optimal configurations are determined by solving a many-objective optimization model. A non-dominated sorting genetic algorithm generation III is employed to solve the many-objective optimization problem. Exergy for water, exergy efficiency, and total product exergy costs, respectively, improved by 3, 3.6, and 3.7 times, while total annual costs decreased by 17.8–50.3% after optimization. Considering the nexus between exergy, water, and economics, the optimal single compressor configuration was recommended for hot and dry regions and the robust double-compressor configuration was recommended for cold climates or general trigeneration.